PENGARUH KUALITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, SISTEM PENGENDALIAN INTERN, PENGAWASAN KEUANGAN DAERAH, DAN KOMITMEN MANAJEMEN TERHADAP KEANDALAN PELAPORAN KEUANGAN PEMERINTAH (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Ben - Putra, Rizki Agus; Azlina, Nur; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This is consistent with the concept of reliability of the information in the financial statements that should be free of errors and misleading understanding of the material, presenting any facts honestly, and can be verified. This study investigated the influence of the quality of human resources, utilization of information technology, internal control, financial control area, management commitment. The sample studied consisted of 36 SKPD in Bengkalis. the analytical techniques used to test hypotheses is purposive sampling. Data were analyzed using multiple regression analysis using SPSS (Statistical Product and Service Solution) version 17. The results showed that the quality of human resources, utilization of information technology, internal control, financial control area, management commitment to have an influence on the reliability of financial reporting of local government , The quality of human resources shows the coefficient of 0.137 with significance value of 0.013. Utilization of information technology shows coefficient 0.247 with a significance value of 0.001. Internal controls showed coefficient 0.126 with a significance value of 0.008. Financial oversight regions shows coefficient 0.140 with a significance value of 0.008. Demonstrated management commitment koefiesn 0.408 with a significance value of 0.000. This decision was made are all variables significantly influence the reliability of financial reporting of local government ,Keyword : Quality resource, Information Technology, Internal Control, Supervision, Management, and reliability of financial.